2000
DOI: 10.1046/j.1365-294x.2000.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

The genetic mating system of spotted sunfish (Lepomis punctatus): mate numbers and the influence of male reproductive parasites

Abstract: In nest-building fish species, mature males often exhibit one of two alternative reproductive behaviours. Bourgeois males build nests, court females, and guard their eggs. Parasitic cuckolders attempt to steal fertilizations from bourgeois males and do not invest in parental care. Previous evidence from the bluegill sunfish (Lepomis macrochirus) suggests that adult males are morphologically specialized for these two tactics. Here, we used microsatellite markers to determine genetic parentage in a natural popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 43 publications
0
32
1
Order By: Relevance
“…These components of reproductive success for males using alternative tactics should not be affected by only selection, but also are likely to vary as a function of factors such as overall male density, relative frequency of males using alternative tactics in a population, and habitat type. Published studies of sperm competition in fish, for example, have already revealed that sperm competition can be intense (22) when multiple male matings occur; however, the frequency of such matings in nature is known for only a few species (10,11,29). As predicted by our model, an increased incidence of multiple male matings should act to delay a Trojan gene effect.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…These components of reproductive success for males using alternative tactics should not be affected by only selection, but also are likely to vary as a function of factors such as overall male density, relative frequency of males using alternative tactics in a population, and habitat type. Published studies of sperm competition in fish, for example, have already revealed that sperm competition can be intense (22) when multiple male matings occur; however, the frequency of such matings in nature is known for only a few species (10,11,29). As predicted by our model, an increased incidence of multiple male matings should act to delay a Trojan gene effect.…”
Section: Resultsmentioning
confidence: 61%
“…After fertilization, eggs were collected from each female and reared until hatching. Medaka fry were then collected, preserved in 100% ethanol, and subsequently dissected to remove the eyes (which often inhibit PCR); their DNA was extracted according to conventional procedures (11). For the parentage analyses, a tetranucleotide microsatellite locus (designated OL1) was developed from a medaka sequence found in the GenBank database (accession no.…”
Section: Methodsmentioning
confidence: 99%
“…For example, DeWoody et al . (1998) demonstrated that sneaker males in the redbreast sunfish ( Lepomis auritus ) were parental males with their own nests, and that sneaking generally yielded low reproductive pay‐offs in this species as well as in the spotted sunfish ( Lepomis punctatus ) (DeWoody et al . 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…Brood parasitism has been detected by paternity analysis in a range of fishes, including cichlids (Dierkes et al 1999;Taborsky 2001), darters (DeWoody et al 2000a), gobies (DeWoody et al 2000bJones et al 2001), and sunfish (DeWoody et al 1998, 2000c. Although brood parasitism may most commonly take the form of male sneaking, genetic analysis has also been used to detect egg thievery, which is known to occur in some species (Largiadèr et al 2001).…”
Section: Breeding Systems and Parental Carementioning
confidence: 99%